Complexo Cultural Sankofa: o espaço construído como facilitador de diálogos e da disseminação da cultura afro-diaspórica na cidade de Manaus. - Monteiro, Clara Luiza Silva (Brasil, 2024)
This final graduation project aims to develop a Cultural Center for afro-diasporic communities in Manaus. Sankofa is an african philosophy that essentially means returning to collect the essential items that have been lost in order to move forward. In this proposal, we sought to create a space where architecture conveys this philosophy of cultural reaffirmation. In the context of Afro-Brazilianness, this implies rescuing elements of architecture practiced in the African continent that suffered erasure during the colonization process as a counter-hegemonic movement with regard to what is known as Brazilian architecture. In this sense, the materiality in this work proposed, has the purpose of providing dialogues and strengthening of the existing Afro-diasporic communities in the city of Manaus, so that they can collectively manage the space to tell their own stories and weave new directions for the preservation of their heritage.